2017
DOI: 10.1007/s40430-017-0721-0
|View full text |Cite
|
Sign up to set email alerts
|

The effect of slip condition on the three-dimensional flow of Jeffrey fluid along a plane wall with periodic suction

Abstract: The laminar flow of an incompressible Jeffrey fluid past an infinite wall is modeled and analyzed analytically considering slip effect. The suction velocity distribution consisting of a basic steady distribution with a superimposed weak transversely varying distribution is assumed. The problem turns out to be three dimension because of variation of suction velocity in transverse direction on the wall. A series expansion technique is employed to obtain approximate solutions for velocity field, skin friction, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…In the future research, the presented BANN-LMT can be used as an effective/accurate stochastic technique for second-grade fluidic system [ 76 ], Casson nanofluid flow model [ 77 ], Jeffrey fluid model [ 78 ], dusty Casson fluid flow model [ 79 ], Darcy–Forchheimer flow model [ 80 ], MHD hybrid fluid flow model [ 81 ] and 2D Sutterby fluid flow model [ 82 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the future research, the presented BANN-LMT can be used as an effective/accurate stochastic technique for second-grade fluidic system [ 76 ], Casson nanofluid flow model [ 77 ], Jeffrey fluid model [ 78 ], dusty Casson fluid flow model [ 79 ], Darcy–Forchheimer flow model [ 80 ], MHD hybrid fluid flow model [ 81 ] and 2D Sutterby fluid flow model [ 82 ].…”
Section: Discussionmentioning
confidence: 99%
“…Amanulla et al 23 obtained the numerical outcomes for the coefficient of skin friction and heat transport analysis of Jeffrey fluid from a vertical inclined plate. Shoaib et al 24 inspected the outcomes of slip condition on Jeffrey fluid along with periodic suction on a plane wall and concluded that the Jeffrey fluid parameters are directing drag force. Reddy et al 25 considered the radiation effect on Jeffrey fluid over an inclined vertical plate.…”
Section: Introductionmentioning
confidence: 99%
“…ere are some non-Newtonian models presenting the three-dimensional fluidic problems though a porous wall with variable suction [31][32][33][34][35]. Periodic suction has received very much attention in the field of aerodynamics [36][37][38].…”
Section: Introductionmentioning
confidence: 99%